Standraidization of Post traumatic Stress Disorder Scale on Students of University of Baghdad (Journal Of Educational and Psychological Researches, 2017)
There are a lot of measures for Post Traumatic Stress Disorder (PTSD), but what distinguishes it from other measures is the number of short paragraphs and concise depending on the classification of American Psychiatric Association (APA), which can be applied by the researchers on a large number, Because the Iraqi society suffered from psychological trauma due to wars, conflicts and occupation and the resulting psychological disorders of the members of Iraqi society, especially post-traumatic stress disorder, as mentioned by many studies and researches.Therefore, the aim of this study was to standardize the PTSD scale for students at Baghdad University. For the Psychologist Fua . E. which was applied in many foreign studies. This measure was applied to a sample of (800) students (400 male, 400 female) from the University of Baghdad.The standardization of this measure has passed through many stages of scientific procedures in this research. This measure has been included in the 23 paragraph in the initial picture. However, after the application of the research procedures of sincerity and stability and statistical operations, there remain 17 paragraphs in its final form. Note that each phrase contains four different alternatives to the level of severity. This measure was consistently high by using the alpha-cronbach and half-flux coefficient. It also used the global application, which was characterized by high public honesty.